The Dual Role of Macropinocytosis in Cancers: Promoting Growth and Inducing Methuosis to Participate in Anticancer Therapies as Targets - Song, Shaojuan; Zhang, Yanan; Ding, Tingting; Ji, Ning; Zhao, Hang (Frontiers in Oncology, 2021)
Macropinocytosis is an important mechanism of internalizing extracellular materials and dissolved molecules in eukaryotic cells. Macropinocytosis has a dual effect on cancer cells. On the one hand, cells expressing Ras gene under the stress of nutrient deficiency can spontaneously produce constitutive macropinocytosis to promote the growth of cancer cells by internalization of extracellular nutrients (such as proteins), receptors, and exosomes. On the other hand, abnormal expression of Ras and drug treatment (such as MOMIPP) can induce a novel cell death associated with hyperactivated micropinocytosis: methuosis. Based on the dual effect, there is immense potential for designing anticancer therapies that target macropinocytosis in cancer cells. In view of the fact that there has been little review of the dual effect of macropinocytosis in cancer cells, herein, we systematically review the general process of macropinocytosis, its specific manifestation in cancer cells, and its application in cancer treatment, including anticancer drug delivery and destruction of macropinocytosis. This review aims to serve as a reference for studying macropinocytosis in cancers and designing macropinocytosis-targeting anticancer drugs in the future.